Legal Certainty of Hospital Service Operations During Pandemic Corona Virus Disease 2019 - Brilian TitaPutri; Cinderella A.N Rieuwpassa; Gede Angga Dharmadiputra; R. HardadiAirlangga; Mokhamad Khoirul Huda (Indian Journal of Forensic Medicine & Toxicology, 2022)
Hospital is health service institution that provides complete individual health services that provideinpatient, outpatient, and emergency services. In operatingservices the hospital is required to havepermit. Permit is granted if it meets the requirements and standards to ensure the safety of patients,hospitals and health workers. The quality of hospital services is tested through the accreditationprocess,it could not be done during pandemic. Therefore, many policies have been issued, includingthe Circular of Health Minister No. HK.02.01/MENKES/455/2020 Year 2020. This circular facilitatesthe permitextension but does not givedetail abouthow to maintain the hospitalquality and services.During pandemic, the surge in Covid patients is not comparable to the hospitalscapabilities that aredifferent such as in the human resources and the facilities and infrastructure. Many hospitals are fullbecause they have to treat Corona Virus Disease 2019 patients, a lot of equipment, rooms and bedsmust be added, but the health workers that workare limited so that health workers have to work extra toserve patients that increase every day. This situation can cause physical and mental fatigue which overtime has impact on health services so that negligence can occur. So hospitals need to make protectionstandards for health workers in addition to legal responsibility for losses caused by health workersaccording to article 46 of the Hospital Law.